A model for cardiopathy induced by Trypanosoma brucei brucei in mice. A histologic and immunopathologic study. - Poltera, A. A. (1980)
The successful induction of pancarditis in mice by the use of Trypanosoma brucei brucei is reported. The sequential analysis of whole-organ sections demonstrated the presence of trypanosomes in the cardiac structures from the fourth week after infection. Parasites predominated on the endocardial and epicardial side but were also present in the valves, the conducting system, and the lymphatic system draining the heart, the latter being particularly evident in late infection. At the time of parasite invasion, deposits of IgM and IgG and of complement (C3) appeared in the tissues. Also at this time parasitemia reached a plateau, and the circulating specific antitrypanosomal antibodies, the serum Ig and C3, as well as the Clq activity, reached pathologic levels. Cellular response followed parasite invasion and appeared to be similar to that described in human African trypanosomiasis. In late infection, the draining lymph nodes showed a marked histiocytic proliferation, and the vessels became convoluted and distended. The suggested pathogenic mechanisms involve immunologic and mechanical factors. It is possible that the immunologic process prepares for a simultaneous or subsequent parasite invasion of the tissues with an associated inflammatory response. The partial obstruction of the lymphatic cardiac draining system probably accounts at least in part for the peculiar distribution of the parasite-induced lesions. A therapeutic trial was unsuccessful, but the persistence of trypanosomes in the tissues when circulating parasites were no longer detectable may account for relapses.